2012
DOI: 10.1039/c1nr11269d
|View full text |Cite
|
Sign up to set email alerts
|

SiO2nanoparticles biocompatibility and their potential for gene delivery and silencing

Abstract: Despite the extensive use of silica nanoparticles (SiO(2)NPs) in many fields, the results about their potential toxicity are still controversial. In this work, we have performed a systematic in vitro study to assess the biological impact of SiO(2)NPs, by investigating 3 different sizes (25, 60 and 115 nm) and 2 surface charges (positive and negative) of the nanoparticles in 5 cell lines (3 in adherence and 2 in suspension). We analyzed the cellular uptake and distribution of the NPs along with their possible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 54 publications
(54 reference statements)
7
92
2
1
Order By: Relevance
“…[28][29][30][31] Consistent with these studies, we observed that particle size affected the cytotoxicity of SiO 2 EN20(R) and SiO 2 EN20(−) NPs, which were, respectively, eleven-and sevenfold more toxic than 100 nm counterparts against U373MG …”
Section: Discussionsupporting
confidence: 76%
“…[28][29][30][31] Consistent with these studies, we observed that particle size affected the cytotoxicity of SiO 2 EN20(R) and SiO 2 EN20(−) NPs, which were, respectively, eleven-and sevenfold more toxic than 100 nm counterparts against U373MG …”
Section: Discussionsupporting
confidence: 76%
“…SiO 2 nanoparticles of different sizes are known to enter cells by active transport 59,60 and were used here to test the blood-brain barrier model, in order to investigate the cellular interactions of the nanoparticles and look for potential evidence of transcytosis. Particle characterisation in assay medium containing 2 % foetal bovine serum (FBS) indicated that 50 nm (nominal diameter) SiO 2 nanoparticles were partially agglomerated when exposed to cells (See Supplementary Table S1).…”
Section: Uptake and Transcytosis Of Plain Sio2 Nanoparticles Of Diffementioning
confidence: 99%
“…Malvindi et al pointed out that SiNPs had good biocompatibility when used in a reasonable concentration range (up to 2.5 nM). 7 However, as they are smaller than cellular organelles, it is increasingly recognized that SiNPs could penetrate the cytomembrane, deposit in mitochondria or even the nucleus, and eventually lead to cell death. [8][9][10][11] It has been confirmed that NPs can systemically translocate to the circulation from the lung.…”
Section: Guo Et Almentioning
confidence: 99%